(untitled) (Dentika: Dental Journal, 2011)
Streptococcus mutans is a major caries-causing bacteria, which can aggregate to form plaques. Nowadays, caries prevention approach in the cellular level can be done through molecular technology by using anti-bacterial, antibodies or addition of remineralization agent such as Casein Phospho Peptide-Amorphous Calcium Fluor Phosphate (CPP-ACFP) as an inhibitor of biofilm formation by Streptococcus mutans. The purpose of this study was to investigate the role of CPPACFP as an inhibitor to the growth of S. mutans, when used in low and moderate caries risk patient. The CPP-ACFP paste was applicated to patients for 60 days. Any caries inhibitory effects were evaluated as the difference of S.mutans count which was analyzed by S. mutans strip count (GC Corp) and colony count was performed with a bacterial culture. The result showed that there was no significant difference between before and after using CPP-ACFP in colony counting by S.mutans stripcount (GC Corp), pH, and buffer capacity from saliva.In conclusion, there was no effect after using CPP-ACFP since user didn’t use it regularly. To expect better result in using CPP-ACFP preventive treatment, we should improve patient’s compliance.